Internalization of Islamic Education Values Through Ruqyah at the Ruqyah Al Hikmat Institute in Sidenreng Rappang Regency - Abd. Rahim; Hamdanah; Muh. Akib D; Hannani; Ambo Dalle (Universitas Muhammadiyah Palu, 2024)
The research entitled Internalization of Islamic Education Values Through Ruqyah at the Ruqyah Al Hikmat Institute in Sidenreng Rappang Regency, aims to: a. Describe the Ruqyah technique applied at the Al Hikmat Ruqyah Institute, b. Describe the process of internalizing Islamic educational values for Ruqyah patients at the Al Hikmat Ruqyah Institute, c. Describe the implications of internalizing Islamic educational values through ruqyah for ruqyah patients at the Al Hikmat Ruqyah Institute. This type of research is field research using qualitative data processing techniques. The research subject is the Internalization of Islamic Education Values and the research object is ruqyah activities carried out at the Rugyah Al Hikmat Institute. Data collection in research includes interviews, observation and documentation. The data collected is carried out by data reduction to select appropriate data, then data interpretation and data presentation are carried out and conclusions are drawn. The research results show; 1) The Ruqyah technique applied at the Al Hikmat Ruqyah Institute includes prayer through the media of water, salt and oil or read directly to the patient, Ruqyah with verses from the Qur'an, Hypnotherapy, motivational advice. 2) The process of internalizing the values of Islamic education for Ruqyah patients at the Al Hikmat Ruqyah Institute includes: The Value Transformation Stage is implemented through a lecture or preaching model involving Aqidah, Morals and Worship. The da'wah is delivered both individually and to audiences such as the patient's family. The da'wah theme is adapted to the patient's needs. The Value Transaction Stage is implemented by establishing two-way communication between the Team, the patient and the patient's family. This communication is not only established directly, but can also be done through other media such as WhatsApp. It can be seen from several observations that Peruqyah has to be patient in listening to his patients' stories and this has an effect on the patient because he can listen to Peruqyah's advice because he feels cared for and never pushed into a corner. The stages of internalization include knowledge and awareness, practice and habituation and characterization of the value of Islamic education in patients. One of the most important factors of internalization is the example that makes an impression on the ruqyah patient so that even without the physical presence of the ruqyah, the preaching and teaching of Islamic values for the patient will continue to be remembered and become a practice which ultimately becomes a character for the patient. 3) This form of internalization has implications on the practice of Islamic values in daily life with full self-awareness and that is part of the characterization that occurs in ruqyah patients, such as there are patients who after recovering no longer leave prayers and even always pray in congregation at the mosque, there are patients who since recovering have not I like to argue or argue with my neighbors